The (im)possibility of communication with nonhuman beings: with digital screen printing of luminous bacteria - Saeki, Takumi; Masuda, Nobuhiro; Jo, Kazuhiro (Frontiers in Communication, 2024)
In the current media environment, John Durham Peters emphasizes the importance of non-verbal communication and notes that underpinned by digital technology, "media" is returning to its original meaning as the milieu that surrounds living beings. To concretize and critically discuss this idea, this paper examines the artworks created by the authors, which incorporate microorganisms into digital technology. These works applied luminous bacteria as ink to digitally screen print text and images. The first work, A Medium for Images or Luminous Bacteria (2022), prints Japanese text with luminous bacteria ink. The second work, 'イ(I) ' (1926) by Bioluminescent Bacteria (2024), recreates the first image in the history of Japanese television, 'イ(I)', with luminous bacteria. This paper compares and analyzes these practices in light of classical media theory, including the work of William Ivins Jr. and Marshall McLuhan. The paper introduces another work, Grow.|Glow (2023), to further expand the discussion to contemporary digital media to expand the discussion to contemporary digital media. Finally, drawing on the recent arguments of Anna Ting and Antonio Damasio, we elucidate the critical implications that the works of luminous bacteria bring to the current media environment. Acknowledging the current situation where digital technology has become our surrounding milieu, it Acknowledging the current situation where digital technology has become our surrounding milieu, it becomes increasingly important to focus on the nonverbal communication that is often overlooked due to the efficiency of these technologies, that is particularly the case when considering communication with non-humans. In effect, Peters draws attention to the fact that "our bodies are embedded in climate history, fire regimes, the spin of the earth, north and south, and relations with plants, artifacts, and organisms of all kinds, especially each other. " (p.380) These ideas are intriguing as they open up the concept of communication, traditionally understood exclusively from a human perspective, to the relation with non-human realm. However, the last point, quoted from the concluding part of Peters' work, sets the agencies of non-verbal communication so broadly, ranging from artifacts to other organisms, that it becomes difficult to pursue a specific discussion.